Antioxidant and Anticarcinogenic Potentials of Propolis for Dimethylhydrazine-Induced Colorectal Cancer in Wistar Rats. (23rd June 2022) - Salehi, Alireza; Hosseini, Seyed Mohammad; Kazemi, Sohrab
Abstract : Propolis is a natural compound with anticarcinogenic properties. The present study aimed to compare the inhibitory effect of ethanolic extract of propolis (EEP) and vitamin E on dimethylhydrazine-induced colon lesions in rats. In this study, 60 rats were randomly categorized into six 10-member groups. After 13 weeks, blood and colon tissue were sampled to examine some factors. The parameters included red (RBC) and white (WBC) blood cell profile, lactate dehydrogenase (LDH), C-reactive protein (CRP), total protein (TP), creatine kinase (CPK), and albumin, as well as the extent of colon histological lesions, protein expression (adenomatous polyposis coli (APC), proliferating cell nuclear antigen (PCNA), carcinoembryonic antigen (CEA), and platelet-derived growth factor (PDGF)), and oxidative stress markers (total antioxidant capacity (TAC), malondialdehyde (MDA), and superoxide dismutase (SOD)) in colon tissue. A significant decrease was observed in congestion, mitotic index, inflammation, and cell destruction in colon tissue in dimethylhydrazine group in comparison with the control group (P < 0.05 ). The EEP exposed rats exhibited a significant lower oxidative stress than the DMH group (P < 0.05 ). Furthermore, the extract significantly affected TAC level (P < 0.05 ). While the expression level of APC rose substantially in the EEP-treated group compared to the DMH group, the level of PCNA, CEA, and PDGF proteins significantly reduced. It seems that the EEP can efficiently prevent DMH-induced colonic lesions. Furthermore, its effectiveness is more than the vitamin E, which is a strong antioxidant.